Artenverlust schmälert Ökosystemleistungen. Ökologische Experimente zeigen die Bedeutung von Artenvielfalt für Ökosystemleistungen. - Meyer, Sebastian; Eisenhauer, Nico (Forum Landschaftsplanung - AbsolventInnenverband, 2020)
The Jena Experiment was set up in 2002 to investigate the effects of manipulated grassland plant diversity (gradient of 1 to 60 species) on element cycling and trophic interactions. Results of 15 years of research indicate that diverse grasslands have high productivity while simultaneously providing multiple additional ecosystem services.
Keywords: Ökosystemleistung; Ökosystem; Artenvielfalt; Landnutzung; Umweltveränderung; Biodiversität; Naturschutz; Artenschutz